Studies on the Occurrence of Viruses in Planting Material of Grapevines in Southwestern Germany - Noemi Messmer; Patricia Bohnert; Stefan Schumacher; René Fuchs (Viruses, 2021)
Viral diseases in viticulture lead to annual losses in the quantity and quality of grape production. Since no direct control measures are available in practice, preventive measures are taken to keep the vines healthy. These include, for example, the testing of propagation material for viruses such as Arabis mosaic virus (ArMV), Grapevine fanleaf virus (GFLV) or Grapevine leafroll-associated virus 1 (GLRaV-1) and 3 (GLRaV-3). As long-term investigations have shown, GLRaV-1 (2.1%) occurs most frequently in southwestern German wine-growing regions, whereas GLRaV-3 (<0.1%) is almost never found. However, tests conducted over 12 years indicate that there is no general decline in virus-infected planting material. Thus, it can be assumed that a spread of the viruses via corresponding vectors still takes place unhindered. Beyond the examinations regulated within the German Wine Growing Ordinance, one-time tests were carried out on Grapevine Pinot gris virus (GPGV). This analysis showed that GPGV was found in 17.2% of the samples.